Relationship between Knowledge and Covid-19 Preventive Measures among Pregnant Women - Safitri Safitri (EMBRIO: Jurnal Kebidanan, 2022)
Covid-19 is an acute respiratory tract infection caused by the SARS-CoV-2 virus and has become a pandemic worldwide. Covid-19 has infected the entire world population including pregnant women. The vulnerability of pregnant women to infectious diseases is due to changes in body physiology and immune response mechanisms. One of the causes of transmission of Covid-19 in pregnant women is the lack of knowledge regarding Covid-19 and its prevention. This study mainly aims to determine the relationship between knowledge and Covid-19 preventive measures among pregnant women in Jambi City. This was an analytical observational study with cross-sectional design. The study population involved all pregnant women in Jambi City, with a total sample of 100 pregnant women, who were selected using a purposive sampling technique based on inclusion and exclusion criteria. Data were collected using online questionnaire from December 2020 to March 2021. Data were analyzed using Chi-Square test. Results of this study showed that knowledge had a significant relationship with Covid-19 preventive measures among pregnant women in Jambi City with a p-value of 0.001 (OR=4.943). Based on the results of this study, it is expected that healthcare workers can provide health education to prevent the risk of Covid-19 transmission among at-risk groups.